DETERMINAN PERSEPSI MAHASISWA AKUNTANSI MENGENAI ETIKA ATAS PENGGELAPAN PAJAK (TAX EVASION) - Erika Aulia Susanto; Muslimin Muslimin (Jurnal Proaksi, 2022)
Tax Evasion is criminal act which applied by taxpayers to reduce the amount of tax charged or not to pay tax illegally. The aim of this study was to find out the factors influencing the ethical perception of accounting students towards tax evasion. The quantitative design is used in this study. The population are the students of accounting major, Economic and Business Faculty, Pembangunan National “Veteran” University East Java and Airlangga University class of 2017 and 2018. The sampling technique using Slovin’s formula, so that it can be obtained 92 respondents. The analysis technic used multiple regressions linier processed using SPSS. The result of this research indicate that the fairness and discrimination has no influence on the ethical perceptions of accounting students towards tax evasion while taxation system has an influence on the ethical perceptions of accounting students towards tax evasion. Keywords: Fairness, Taxation Systems, Discrimination